2012
DOI: 10.1136/bmjopen-2012-001257
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of anal incontinence among Norwegian women: a cross-sectional study

Abstract: ObjectiveAnal incontinence (AI) is a symptom associated with age, bowel symptoms and obstetric injuries. Primary aim of the study was to establish the prevalence of AI among women and secondarily to evaluate the impact on daily life and conditions associated with AI.DesignA cross-sectional study.SettingParticipants attended research stations located in different parts of Nord-Trøndelag county, Norway. Data were collected through interviews, questionnaires and clinical examinations.ParticipantsIn total, 40 955 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 36 publications
4
51
1
Order By: Relevance
“…there was wide variation in specific factors assessed and the way that associations were determined, with some studies reporting univariate analyses alone and other studies reporting results of multivariate modeling. overall, the 3 most commonly reported factors associated with fi were increasing age, 4,14-16,18,23-25,30,36,39,42 diarrhea and/or fecal urgency, [14][15][16]18,19,24,27,41 and urinary incontinence and/or overactive bladder 13,14,17,18,21,25,32,39 (table 4). the 3 most commonly reported factors not associated with fi were obstetric history or previous obstetric trauma, [13][14][15]18,21,32,36 sex, 14,16,27,40,42 and constipation and/or hard stools 15,16,18,19 (table 4).…”
Section: Prevalence Estimates For Fimentioning
confidence: 99%
See 2 more Smart Citations
“…there was wide variation in specific factors assessed and the way that associations were determined, with some studies reporting univariate analyses alone and other studies reporting results of multivariate modeling. overall, the 3 most commonly reported factors associated with fi were increasing age, 4,14-16,18,23-25,30,36,39,42 diarrhea and/or fecal urgency, [14][15][16]18,19,24,27,41 and urinary incontinence and/or overactive bladder 13,14,17,18,21,25,32,39 (table 4). the 3 most commonly reported factors not associated with fi were obstetric history or previous obstetric trauma, [13][14][15]18,21,32,36 sex, 14,16,27,40,42 and constipation and/or hard stools 15,16,18,19 (table 4).…”
Section: Prevalence Estimates For Fimentioning
confidence: 99%
“…overall, there were only 3 studies meeting 4 or more of the high-quality criteria that investigated the prevalence of fi among a representative sample of adult community dwellers, that is, among men and women aged ≥18 years. 12,14,16 Study Aims and Design of the 32 studies reporting a prevalence of fi, 12 studies had the primary aim of determining the community prevalence of fi in isolation, [12][13][14][15][16][17][18][19][20][21]23,29 whereas 13 studies investigated prevalence of fi in combination with rates of urinary incontinence, 24 35 and 2 studies aimed to correlate rates of incontinence with mortality 30 and functional status 26 ; in each of these latter studies, prevalence rates of fi were reported as a secondary outcome measure. all of the studies were population-based, cross-sectional studies, except for 1 study performed by adolfsson et al, 37 which was a case-control study.…”
Section: Studies Reporting Prevalence Of Fimentioning
confidence: 99%
See 1 more Smart Citation
“…2,11,13,17,41 Other conditions associated with FI include advanced age, disease burden (comorbidity count, diabetes), anal sphincter trauma (obstetrical injury, prior surgery), and decreased physical activity. 11,16,17,42,43 Several diseases that affect anorectal sensorimotor dysfunctions and/or alter bowel habits are also associated with FI in clinical practice (Table 2). Some of these conditions do not emerge as risk factors in community studies, possibly because their prevalence is relatively low.…”
Section: F1 Fecal Incontinencementioning
confidence: 99%
“…The mechanisms by which obesity predisposes to FI are incompletely understood (62). Other conditions associated with FI include advanced age, disease burden (co-morbidity count, diabetes), anal sphincter trauma (obstetrical injury, prior surgery), and decreased physical activity (3, 9, 13, 17, 63). …”
Section: Etiology Associated Conditions and Risk Factorsmentioning
confidence: 99%